PENGARUH INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KRIMINALITAS DI KALIMANTAN BARAT DALAM KERANGKA EKONOMI ISLAM - Aya Sofia Ardelia (JURNAL MUAMALAT INDONESIA - JMI, 2023)
This study aims to analyze the effect of the human development index on crime rates in West Kalimantan Province within the framework of Islamic economics. Quantitative approach is used in this research. The analytical method used is Panel Data Regression. The data used in this study is data on all regencies/cities in West Kalimantan Province for the period 2010 to 2016. The results of the study show that the best model for estimation in this study is the Fixed Effect Model (FEM). The influence of HDI on the crime rates shows a significant negative effect, which means that the higher the HDI, the lower the crime rates and vice versa. In addition, the HDI concept, which consists of 3 main dimensions, namely health, education and income, is very close to the maqashid sharia concept of Islamic economics, namely hifdzunnafs (safeguarding the soul), Hifdzunnaql (preserving the mind) and hifdzulmal (preserving wealth).